HLA-linked genes and islet-cell antibodies in diabetes mellitus. Issue 6025 (26th June 1976) - Lendrum, R; Walker, G; Cudworth, A G; Woodrow, J C; Gamble, D R
Abstract : In a random series of 139 insulin-dependent diabetics aged 30 or under at the onset of disease islet-cell antibody (ICA) was detected in 33 cases (24%). In 27 patients who had had diabetes for less than one year 16 (59%) had ICA. Only one out of 51 patients with maturity onset diabetes who were not dependent on insulin were positive for ICA. Four out of 19 patients with late onset insulin-dependent diabetes had ICA. There was no association between the presence of ICA and any particular HLA phenotype. Within families containing two or more HLA haploidentical siblings with juvenile onset diabetes ICA was a variable finding both in its occurrence and in its relation to the duration of disease. A possible mode of action for the HLA-linked gene may be to permit a rapid immunological destructive process, possibly associated with viral infection.